Gramsci and Machiavelli: Jacobinism Mediating the Prince’s Movement - Del Roio, Marcos [UNESP] (My University, 2022)
Gramsci lamented that four centuries after Machiavelli’s death, the teachings of his short book The Prince, produced in 1513, hadn’t yet become common sense, in other words, had not yet been incorporated by the popular masses.